Infection Prevention and Control Knowledge among Health Sciences Students: A Cross-Sectional Study from Malaysia - Abdul Rahman Fata Nahas; Hanis Zulaikha Samsuri; Muhammad Eid Akkawi; Mohamed Hassan Elnaem; Tarek El Sayed; Nor Hidayah Mohd Taufek; Abdulkareem Mohammed Al-Shami (Journal of Pharmacy, 2024)
Introduction: Infection prevention and control (IPC) is a crucial component of the healthcare system that demands adherence to standards to avoid and reduce the risk of infectious diseases spreading among patients, staff members, and visitors to healthcare institutions. The aim of this study was to assess IPC knowledge among undergraduate health sciences students and to identify the critical IPC components that need to be addressed. Methods: A cross-sectional online survey was conducted among 235 final-year health science students at International Islamic University Malaysia (IIUM), involving five faculties: the Faculty of Medicine, Dentistry, Pharmacy, Nursing, and Allied Health Science. A 45-item questionnaire was used to collect participants’ sociodemographics (5 items) and explore their knowledge about IPC across six aspects (40 items). A score of > 24 (62%) indicates satisfactory knowledge. Results: The majority of the participants were female (74.9%), and 34% were from the Faculty of Pharmacy. Medicine students had the highest level of IPC knowledge with a mean score of 29.3 (n = 52), which was significantly different from Allied Health Science students (M = 25.6, n =55, p < 0.001). Other faculties students had similar IPC knowledge with no significant differences (Pharmacy: M = 27.5, n = 80; Nursing: M = 27.4, n = 29; Dentistry: M = 27.2, n = 19). IPC components that need to be improved are knowledge about sharp disposals and sharp injuries, as well as respiratory hygiene and cough etiquette. Conclusion: IPC knowledge was adequate among health science students at IIUM, although certain IPC components still require improvement. Additional IPC educational materials and workshops should be added to all faculties' syllabi to address this issue.